Functional and structural characterization of the pentapeptide insertion of Theileria annulata lactate dehydrogenase by site-directed mutagenesis, comparative modeling and molecular dynamics simulations - MUTLU, ÖZAL (ELSEVIER SCIENCE INC, 2017)
Lactate dehydrogenase (LDH) is an important metabolic enzyme in glycolysis and it has been considered as the main energy source in many organisms including apicomplexan parasites. Differences at the active site loop of the host and parasite LDH's makes this enzyme an attractive target for drug inhibitors. In this study, five amino acid insertions in the active site pocket of Theileria annulata LDH (TaLDH) were deleted by PCR-based site-directed mutagenesis, expression and activity analysis of mutant and wild type TaLDH enzymes were performed. Removal of the insertion at the active site loop caused production of an inactive enzyme. Furthermore, structures of wild and mutant enzymes were predicted by comparative modeling and the importance of the insertions at the active site loop were also assigned by molecular docking and dynamics simulations in order to evaluate essential role of this loop for the enzymatic activity. Pentapeptide insertion removal resulted in loss of LDH activity due to deletion of Trp96 and conformational change of Arg98 because of loop instability. Analysis of wild type and mutant enzymes with comparative molecular dynamics simulations showed that the fluctuations of the loop residues increase in mutant enzyme. Together with in silico studies, in vitro results revealed that active site loop has a vital role in the enzyme activity and our findings promise hope for the further drug design studies against theileriosis and other apicomplexan parasite diseases. (C) 2017 Elsevier Inc. All rights reserved.
Keywords: Site-directed mutagenesis; Lactate dehydrogenase; Homology modeling; Molecular dynamics simulation; Theileria annulata; PLASMODIUM-FALCIPARUM; ACTIVE-SITE; PROTEINS; ELECTROSTATICS; BUPARVAQUONE; PARASITES; DESIGN; VIVAX; GENE